2014
DOI: 10.1103/physreva.90.063802
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional atom localization by laser fields in a four-level tripod system

Abstract: We present a scheme of the high-precise three-dimensional (3D) localization by the measurement of the atomic-level population. The scheme is applied to a four-level tripod-type atom coupled by three strong standing waves and a probe running wave. As a result, the atom can be localized in volumes that are substantially smaller than a cubic optical wavelength. The upper-level distribution depends crucially on the atom-field coupling and it forms 3D periodic structures composed of spheres, hourglasses, bowls, don… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 34 publications
0
68
0
Order By: Relevance
“…It is found that the precision and resolution of the 3D atom localization can be significantly improved due to the spacedependent atom-field interaction. More importantly, the 3D atom localization patterns reveal that the maximal probability of finding an atom within the sub-half-wavelength domain of the standing waves can reach 100 %, which is increased by a factor of 4 or 8 compared with the previous proposed schemes [35,36]. As a result, our scheme may be helpful in realizing spatially selective single-qubit phase gate, entangling gates between cold atoms, and error budget for the single-qubit phase gate in three dimensions.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It is found that the precision and resolution of the 3D atom localization can be significantly improved due to the spacedependent atom-field interaction. More importantly, the 3D atom localization patterns reveal that the maximal probability of finding an atom within the sub-half-wavelength domain of the standing waves can reach 100 %, which is increased by a factor of 4 or 8 compared with the previous proposed schemes [35,36]. As a result, our scheme may be helpful in realizing spatially selective single-qubit phase gate, entangling gates between cold atoms, and error budget for the single-qubit phase gate in three dimensions.…”
Section: Discussionmentioning
confidence: 96%
“…In order to deal with the above problem, here we put forward a scheme to realize efficient 3D atom localization based on the measurement of spontaneous emission in a three-level atomic system. The work is mainly based on [35,36]; however, our scheme shows more advantages that the two schemes do not have. First, we show that efficient 3D localization is realistically possible with only three atomic levels, and that one obtains interesting patterns around points of localization by a simple tuning of the parameters of the system.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A four-level tripod-type atomic system is also proposed to achieve a high-precision two-dimensional atom localization via measurement of the excited state population [40]. Yet the three-dimensional (3D) atom localization has been investigated only in few proposals [43][44][45]. Compared to the 1D and 2D localization, the 3D localization of an atom gives a more specific information about the position of a moving atom.…”
Section: Introductionmentioning
confidence: 99%